HOUSING PREFERENCES OF FULL NEST 1 LIFECYCLE STAGE CUSTOMERS IN RESPONSE TO THE PANDEMIC - Tjiputra, Luisa Hartono; Sutrisno, Timotius FCW (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2022)
The purpose of this study is to define customer preferences for housing, especially customers who belong to the Full Nest 1 group in a family’s life cycle. The subject examined in this study focuses on the interior design and architecture industry in Surabaya, East Java. As a result of COVID-19, there has been a massive impact on the development sector which affected these industries. This is because both industries relied on face-to-face interactions to function. However, after the application of new regulations as a response to the pandemic, several changes are to be made regarding client interaction and project management. The effect of large-scale social distancing has affected operations, and caused a shift in customer’s preferences. This study uses a quantitative approach, in which changes in customer preferences are obtained through interviews with relevant sources in order to narrow down prioritized factors. The data is then processed through factor analysis, and is distributed as a survey to 30 respondents representing the Surabaya region. The data collection process of this research is carried out with a ranking scale and processed using the Conjoint analysis to understand the current priorities of customers in response to the pandemic.